Long-term Masogastric Feeding and Complications of Acute Gastric Ulcer in Two Elderly Patients - Yoshimine, Noboru; Miura, Satoru; Funaki, Chiaki; Hayashi, Toshio; Goto, Tsutomu; Ando, Fujiko; Kuzuya, Fumio (Nihon Rōnen Igakkai zasshi, 1992)
Some elderly patients with chronic illness such as stroke, or Parkinsonism cannot take food orally because of dysphagia. In such cases, tube feeding can be used as a supplement to oral intake when malnutrition is present. This route allows for easier nursing care and decreases the frequency of aspiration pneumonia. Complications of tube feeding include nutrient deficiency states, pulmonary aspiration, gastrointestinal and metabolic disorders. We report two cases with complications of acute gastric ulcer which was thought to be induced with long-term tube feeding. Case 1 was a 61-year-old male patient with Parkinson's disease for ten years. L-DOPA had been administered with good control of his condition. However, his ability to swallow has deteriorated gradually. As he often suffered from aspiration pneumonia, nasogastric tube feeding was performed. After three years of tube feeding, he suddenly vomited much bloody material. He died from massive bleeding with acute gastric dilatation. Autopsy showed giant acute gastric ulcer covered with coagulated blood. UL3, 50mm in maximum diameter, was observed in the middle portion of the greater curvature, where the top of tube probably came in contact with the gastric wall. Case 2 was an 83-year-old female patient with stroke and chronic heart failure. She had been hospitalized for about one year because of the intermittent deterioration of her cardiac condition. Furthermore, her inability to swallow increased during her hospitalization. She also suffered from aspiration pneumonia. Nasogastric tube feeding was performed to prevent aspiration pneumonia and malnutrition. She died of acute heart failure after twelve months. Autopsy revealed heart dilatation, old myocardial infarction and stroke. In addition, two acute gastric ulcers (UL3, 10 and 30mm in diameter) were recognized; one was in the upper portion of the greater curvature, the other in the lower portion of the greater curvature. The location of these gastric ulcers was unusual. Moreover, they concided with location of top of the nasogastric tube. From these two cases, we conclude that in long-term tube feeding the tip of the tube often comes in contact with the gastric wall, and gastric ulcer could be produced by repeated mechanical stimulus of the wall. Reports of acute gastric ulcer induced by tube feeding have not been published previously. Therefore, we should pay much attention to this complication in the care of the elderly people with long-term tube feeding.